Callosal projections in rat somatosensory cortex are altered by early removal of afferent input. - Koralek, K A (1990)
During the first postnatal week, the distribution of callosal projection neurons in the rat somatosensory cortex changes from a uniform to a discontinuous pattern. To determine if this change is influenced by afferent inputs to the somatosensory cortex, the effect of both early unilateral infraorbital nerve section and unilateral removal of the dorsal thalamus on the distribution of callosal projections in rat somatosensory cortex was examined. One month after either of the above manipulations at birth, the tangential distribution of callosal projections in the somatosensory cortex was examined using the combined retrograde and anterograde transport of horseradish peroxidase. Both manipulations alter the distribution of callosal projection neurons and terminations in the somatosensory cortex. After infraorbital nerve section, the distribution of callosal projections is altered in the contralateral primary somatosensory cortex. The abnormalities observed are consistent with the altered distribution of thalamocortical projections. In addition, consistent abnormalities were observed in the pattern of callosal projections of the second somatosensory area of both hemispheres. Most notably, they are absent in a portion of the region that contains the representation of the mystacial vibrissae and sinus hairs in this area. Thalamic ablation resulted in highly aberrant patterns of callosal projections in the somatosensory cortex on the operated side, where abnormal bands and clusters of callosal projections were observed in apparently random locations. These results are interpreted as evidence that both peripheral and central inputs influence the maturational changes in the distribution of callosal projection neurons.